Vulneración del derecho a la defensa en la junta mancomunada de protección de derechos niñez y adolescencia frente sur occidental Tungurahua - Luzmila Cleofe, Tisalema Jinde (2021)
SUMMARY Article 76 of the Constitution of the Republic of Ecuador guarantees due process; and, within it, some guarantees of the right to defense are established, the same that must be observed by public entities in all judicial proceedings, as well as in administrative proceedings where the rights of individuals may be affected. For this reason, in the present investigation, an analysis was carried out of the administrative procedure carried out in the Joint Boards for the Protection of Rights of the Municipal Gads Western South Front of the Province of Tungurahua. This process is being carried out to achieve the protection of the Board. For this reason, in the present investigation, an analysis was carried out of the administrative procedure carried out in the Joint Boards for the Protection of Rights of the Municipal Gads Western South Front of the Province of Tungurahua. This process is being carried out to achieve the protection of the Board. It was possible to show that in the administrative procedures for the protection of children's rights processed in the Joint Boards, some of the guarantees of due process, nor the right to defense since a unified procedure is not carried out, sometimes the accused is heard before issuing the administrative protection measures, in other cases not. The right of contradiction is limited, which leaves evidence that the right to defense is sometimes not considered in the administrative procedures, which causes the violation of the accused's rights. Keywords: Childhood, Rights, Joint Boards, Due Process, Defense Translation Reviewed By: MSc Elizabeth Diaz English Professor 0603277765